Self‐Assembly of Cyclohelicate [M3L3] Triangles Over [M4L4] Squares, Despite Near‐Linear Bis‐terdentate L and Octahedral M. Issue 57 (19th July 2017) - Hogue, Ross W.; Dhers, Sébastien; Hellyer, Ryan M.; Luo, Jingwei; Hanan, Garry S.; Larsen, David S.; Garden, Anna L.; Brooker, Sally
Abstract: Self‐assembly of 1:1:2 M II (BF4 )2 (M=Zn or Fe), pyrazine‐2, 5‐dicarbaldehyde (1 ) and 2‐(2‐aminoethyl)pyridine gave trimetallic triangle architectures rather than the anticipated tetrametallic [2×2] squares. Options for the nontrivial synthesis of1 are considered, and synthetic details provided for both preferred routes. Rare cyclohelicate triangle architectures are observed for the pair of structurally characterized yellow‐brown [Zn3 L 3 ](BF4 )6 and dark green [Fe3 L 3 ](BF4 )6 complexes of the neutral bis‐terdentate Schiff baseL . In order to form these pyrazine‐edged triangles, the octahedral metal ions—with all 6 N‐donors provided by the terdentate binding pockets of twoL —are located 0.4–0.5 Å out of the plane of the bridging pyrazines, towards the center of the triangle. Density functional theory calculations confirm that simple particle counting entropic arguments, which predict triangles over squares, are correct here, with the triangles shown to be energetically favored over the corresponding squares. However, importantly, DFT analysis of these and related triangle versus square systems also show that vibrational contributions to entropy dominate and may significantly influence the preferred architecture, such that simple particle counting cannot in general be reliably employed to predict the observed architecture. Abstract : Rare cyclohelicate triangle architectures, not squares as seen for the bis‐terdentate di‐amide ligand, self‐assemble when the di‐imine analogue is employed. In the triangles, the octahedral metal ions are located 0.4–0.5 Å out of the plane of the bridging pyrazine rings, towards the center of the triangle. DFT calculations correctly predict the observed triangle architectures to be energetically favored (see scheme).